APLIKASI KONSEP FIQH SOSIAL KH. M.A. SAHAL MAHFUDH TERHADAP BATAS USIA PERKAWINAN DALAM PASAL 7 AYAT (1) UNDANG-UNDANG PERKAWINAN - Muh. Luthfi Hakim (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2019)
The limitation age of marriage in article 7 verse (1) of Law Number 1/1974 on marriage, is considered to cause various problems. The limitation age for marriage of 19 for males and 16 years for females is too early and it is less appropriate with biological, psychological, educational, and economic maturity. Psychologically, marriages under 21 years of age do not yet have maturity. From the aspect of the fulfillment of economic needs, a husband is still not stable to meet family needs.The purpose of this research is to analyze the limitation age of marriage in Law Number 1/1974 by using perspective madzhab qauli fiqh sosial KH . MA. Sahal Mahfudh and analyze the minimum age of marriage in Law Number 1/1974 by using perspective manhaji fiqh sosial KH . MA. Sahal Mahfudh. The results of this research indicate that: First, the madzhab qauli of fiqh sosial sees the limitation age of marriage is too low and not in accordance with the condition that exist in society, and it will cause to adverse impacts. Therefore the preventive effort has to be done, it is in accordance with the rules of fiqh ad-daf'u aqwā min ar-raf'i. Secondly, the madzhab manhaji of fiqh sosial through the the theory of masālikul illat say that the limitation age of marriage in Law Number 1/1974 must be integrated with the purpose of marriage and create al-maslaḥah al-‘āmmah. Keywords: The limitation age of marriage, Law Number 1/1974, Fiqh Sosial.